Microplastic Contaminations in Buffet Food from Local Markets - Tokhun, Natsima; Somparn, Atcharaporn (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 4 (2020): October-December-2020, 2020)
Microplastics are environmental problems at global level, which can be primary environmental risks associated with food contaminations. Therefore, this study aims at determining contamination of microplastics in buffet food at three local markets in Ayutthaya and Pathum Thani, Thailand. This research investigated the contamination of microplastics in buffet food at three fresh markets. The results found the highest contamination 16 pieces/5g of tissue (wet weight) from mussel and fish tofu samples. The evaluation of consumption was consuming 1 kilogram of food could receive 3,200 microplastics of contamination that representing 13.01% from 11 types of microplastic. Moreover, the microplastic contamination also found the highest level in seafood (833 + 159 pieces/1 kg of tissue). Approximate 40.65% of the food products from the delicatessen type and products from meat were contaminated the microplastic by average 30.89% and 28.46%, respectively. Most microplastic contamination shad blue color and consisted of multiple types of microplastic, including fibers, fragments, microbeads, rods and pellets, respectively. Consequently, the presence of microplastics in buffet food especially in seafood should be concern about the potential effect of microplastics on human health, impact on food safety and socio economic wellbeing. This research obtained data that will be useful for consumers to consider options of the buffet food and to reduce health risk in long–term. Keywords: microplastic, buffet food, food contamination, plastic packaging, plastics